1996
DOI: 10.1021/ma9517355
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Analysis of Methyl−Phenyl−Siloxane Chains

Abstract: The conformational energy of chain fragments of poly(methylphenylsiloxane) is studied, considering contributions from bond stretching, bond angle bending, bond torsion, and van der Waals interactions. Energy is minimized without constraints, so that minima correspond to fully relaxed conformations. The energy minima of this phenyl-substituted polymer differ notably from those of the parent poly(dimethylsiloxane), due to the importance of the attractive interactions between pairs of phenyl groups. For two repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…In this context it should be noted that the influence of phenyl-phenyl stacking upon the conformational properties of PMPS has been described from a theoretical perspective by Mark [18]. Horta and coworkers also studied the conformational analysis of the methylphenylsiloxane chain (by computer simulation) and found that a stable conformation occurs when a pair of the phenyl rings are facing each other but are not perfectly parallel [19,20]. Hence, it is proposed that the formation of phenyl-phenyl interactions in the system described here may impede the backbiting reaction in PMPS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context it should be noted that the influence of phenyl-phenyl stacking upon the conformational properties of PMPS has been described from a theoretical perspective by Mark [18]. Horta and coworkers also studied the conformational analysis of the methylphenylsiloxane chain (by computer simulation) and found that a stable conformation occurs when a pair of the phenyl rings are facing each other but are not perfectly parallel [19,20]. Hence, it is proposed that the formation of phenyl-phenyl interactions in the system described here may impede the backbiting reaction in PMPS.…”
Section: Resultsmentioning
confidence: 99%
“…The products were carefully analyzed by 19 F-NMR [13,14]. After being crosslinked using covalent bonds, it was shown that the resulting stereoregular PMTFPS elastomeric networks exhibited strain-induced crystallization as shown by WAXS 10 and also by upturns in modulus at high elongations in their equilibrium stress-strain properties.…”
Section: Introductionmentioning
confidence: 99%
“…The force ®eld was the same as described before when reporting conformational energy maps. 5 The dielectric constant was 1.7, for the reasons given there. 5 The temperature for molecular dynamics was 300 K (the SiÐO backbone is very¯exible, so enough transitions occur without the need to go to a higher T).…”
Section: Methodsmentioning
confidence: 99%
“…5 The dielectric constant was 1.7, for the reasons given there. 5 The temperature for molecular dynamics was 300 K (the SiÐO backbone is very¯exible, so enough transitions occur without the need to go to a higher T). The molecular structure is ®rst optimized until minimum energy (with a criterion of 0.001 for maximum derivative).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation